1990
DOI: 10.1007/bf00314808
|View full text |Cite
|
Sign up to set email alerts
|

A single dose desensitization for summer hay fever

Abstract: A new type of desensitising vaccine, enzyme potentiated was subjected to a double-blind randomised study during the hay fever season. The vaccine is a convenient single injection given in March and the results show good protection throughout the grass pollen season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We considered other possible explanations for finding no treatment effect for enzyme potentiated desensitisation whereas six other placebo controlled studies have had positive findings,4 7 – 11 but we were unable to reach a conclusion. Our study population seems to have been of similar average age, although insufficient data were available from the other studies to allow us to establish if the participants were more severely affected or if they were more likely to be sensitive to multiple pollens.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…We considered other possible explanations for finding no treatment effect for enzyme potentiated desensitisation whereas six other placebo controlled studies have had positive findings,4 7 – 11 but we were unable to reach a conclusion. Our study population seems to have been of similar average age, although insufficient data were available from the other studies to allow us to establish if the participants were more severely affected or if they were more likely to be sensitive to multiple pollens.…”
Section: Discussionmentioning
confidence: 82%
“…Each active injection was in the same form and dosage as had been given in the previously reported trials of enzyme potentiated desensitisation in hay fever 4 7 – 11. This consisted of 200 Fishman units of β glucuronidase (derived from the mollusc Haliotis ), 50 pg of 1,3-cyclohexanediol, 50 ng of protamine sulphate, and mixed inhaled allergen extracts (pollen mixes for trees, grasses, and weeds; a mix of allergenic mould spores; cat and dog danders; dust and storage mites) in a total volume of 0.05 ml of buffered saline.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several small but poorly reported RCTs using EPD based on mixed inhalant allergens suggested effectiveness in seasonal allergic rhinitis due to grass pollen [12–15] and childhood house dust mite allergy [16], although a larger and more fully reported clinical trial failed to confirm the results for seasonal allergic rhinitis [17]. Single studies have shown positive results using mixed food allergens for childhood attention deficit disorder [18] and childhood migraine [19].…”
Section: Introductionmentioning
confidence: 99%